1999
DOI: 10.1111/j.1478-3231.1999.tb00040.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary sclerosing cholangitis (PSC): clinical, laboratory and survival analysis in children and adults

Abstract: The present findings on PSC suggest a more severe activity of the disease in children than in adults at presentation; nonetheless, the prognosis seems to be better in children than in adults. The Mayo score prognostic index does not predict the development of liver/colonic cancer. A poor outcome (defined as death or being listed for OLTx) only occurred in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 22 publications
5
22
0
Order By: Relevance
“…This proportion is greater than the 28% prevalence reported by others using different diagnostic criteria, 5 and substantially greater than the 7.1% to 10.6% prevalence found in the adult population using the same international scoring system. 9,21,22 These reports, [4][5][6]20 along with the current study, suggest that the expression of PSC in children is skewed toward a hepatic presentation instead of a predominantly cholestatic profile as occurs in the adult population. Whether this difference represents changes occurring in immune homeostasis with maturity or a longer environmental exposure to putative antigens remains elusive at this time.…”
Section: Discussionsupporting
confidence: 60%
“…This proportion is greater than the 28% prevalence reported by others using different diagnostic criteria, 5 and substantially greater than the 7.1% to 10.6% prevalence found in the adult population using the same international scoring system. 9,21,22 These reports, [4][5][6]20 along with the current study, suggest that the expression of PSC in children is skewed toward a hepatic presentation instead of a predominantly cholestatic profile as occurs in the adult population. Whether this difference represents changes occurring in immune homeostasis with maturity or a longer environmental exposure to putative antigens remains elusive at this time.…”
Section: Discussionsupporting
confidence: 60%
“…Bile duct epithelium frequently shows degenerative changes. In our experience, most children present with histologically advanced disease, mirroring the experience of Floreani and colleagues, who found that children with PSC tended to present with a greater severity of clinical and histologic activity than adults (Floreani et al 1999b ). 10.14 b ).…”
Section: Pathologysupporting
confidence: 83%
“…PSC is another chronic liver disorder shown by inflammatory destruction of small intrahepatic bile ducts as well as extrahepatic bile ducts. 118 PSC is strongly related to inflammatory bowel disease, colorectal cancer, osteoporosis, and cholangiocarcinoma. 119, 120, 121 The role of specific gene deficiencies in the susceptibility to immune-mediated cholangiopathies is highlighted.…”
Section: Etiology and Mechanisms Of Hepatic Apoptosismentioning
confidence: 99%